2010
DOI: 10.1038/hr.2010.170
|View full text |Cite
|
Sign up to set email alerts
|

Association of albuminuria and reduced estimated glomerular filtration rate with incident stroke and coronary artery disease in patients with type 2 diabetes

Abstract: It is unclear whether albuminuria and reduced glomerular filtration rate (GFR) independently increase the risk of incident stroke and coronary artery disease (CAD) in Japanese patients with diabetes. We investigated the independent effects of albuminuria and estimated GFR (eGFR) on the first occurrence of stroke and CAD in patients with type 2 diabetes mellitus (T2DM). We studied 1002 T2DM patients with eGFR (ml min À1 per 1.73 m 2 ) X15 and had no previous cardiovascular disease (CVD) history. GFR was estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 26 publications
(29 reference statements)
4
33
0
Order By: Relevance
“…We confirmed in our cohort the association of MA with the general cerebrovascular risk factors such as diabetes, atrial fibrillation, glucose level upon admission, age and chronic kidney disease reported in previous studies [13,14]. Interestingly, we found a significant association between MA and CRP levels.…”
Section: Discussionsupporting
confidence: 80%
“…We confirmed in our cohort the association of MA with the general cerebrovascular risk factors such as diabetes, atrial fibrillation, glucose level upon admission, age and chronic kidney disease reported in previous studies [13,14]. Interestingly, we found a significant association between MA and CRP levels.…”
Section: Discussionsupporting
confidence: 80%
“…Recent evidence shows that, even before progression to end stage kidney disease (ESKD) requiring hemodialysis or renal transplantation, mild renal impairment and microalbuminuria are independent risk factors for atherosclerotic cardiovascular disease (CVD), such as myocardial infarction and stroke 1) . CKD is a disease concept advocated to encourage the early detection of kidney disease to avoid the development of CVD and progression to ESKD among the constantly increasing numbers of patients with longterm kidney damage.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the number of vessels involved was associated with an incremental increase in the amount of albumin excreted and this was statistically significant. Previous studies had concluded that the clinical outcomes were poorer in the albuminuric group as compared to the non albuminuric counterparts 7,8,9 , however, none of the studies demonstrated the relationship between the amount of albuminuria and the severity of obstruction of coronary arteries despite the fact that they used albumin creatinine ratio in the place urine spot albumin assay 10 . In acute coronary syndrome patients, if the other causes for albuminuria can be excluded, urinary dipstick albumin may be a useful tool to assess the likely severity of obstruction of coronary artery occlusion.…”
Section: Discussionmentioning
confidence: 99%